1982
DOI: 10.1177/000348948209100420
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal Paralysis in Children

Abstract: The charts of 100 children with laryngeal paralysis were reviewed. The patients in this study had either unilateral or bilateral abductor vocal cord paralysis. The literature and pathophysiolof,ry are reviewed. A statistical analysis of each group of patients according to etiology is reported. The follow-up, progress and recovery are detailed. The need for observation and conservative therapy isreinforced by the tendency for spontaneous recovery. Suggestions regarding treatment are given.Kirsch et aF in 1967 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…The incidence of bilateral vocal fold paralysis in infants is unknown as the reports from North America (Holinger et al, 1976;Cohen et al, 1982;Gentile et al, 1986;Tucker, 1986) and France (Narcy et al, 1990) have been from tertiary referral centres with an ill-defined catchment area. Our paediatric airways practice serves a population of 750 000 and in the decade studied 11 (10 per cent) of the infants, under one year, undergoing direct laryngoscopy for stridor had bilateral vocal fold paralysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of bilateral vocal fold paralysis in infants is unknown as the reports from North America (Holinger et al, 1976;Cohen et al, 1982;Gentile et al, 1986;Tucker, 1986) and France (Narcy et al, 1990) have been from tertiary referral centres with an ill-defined catchment area. Our paediatric airways practice serves a population of 750 000 and in the decade studied 11 (10 per cent) of the infants, under one year, undergoing direct laryngoscopy for stridor had bilateral vocal fold paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral vocal fold paralysis in infants is an uncommon but potentially life-threatening condition (Holinger et al, 1976). Previously the majority of cases have been managed with a tracheostomy (Cohen et al, 1982;Gentile et al, 1986;Tucker, 1986;Swift and Rogers, 1987;Narcy et al, 1990). It has, however, been our policy to avoid tracheostomy where possible, and we present our experience of 11 cases over a ten-year period.…”
Section: Introductionmentioning
confidence: 96%
“…Although differences in the rate of tracheostomy for various etiologies have not yet been identified, previous studies that involved multiple etiologies have also reported a higher rate of tracheostomy. [7,911,18]…”
Section: Discussionmentioning
confidence: 99%
“…Intubation is necessary in most of the cases. While older publications mention tracheostomy as unique and permanent therapeutic option, more recent articles also recommend endolaryngeal surgery, e. g. partial unilateral laser chordotomy modified according to Kashima 17 18 19 20 21 22 . Spontaneous regeneration of the vocal fold mobility within the first 12 months of life have been described 23 so that interventions that might have irreversible consequences in the sense of scarring and dysphonia are recommended only after the 12 th month of life 24 .…”
Section: Malformationsmentioning
confidence: 99%